Signet Cell Carcinoma of Colon in a Nineteen-Year-Old Patient: A Case Report. (19th February 2013) - Pamukçu, Özgül; Selcukbiricik, Fatih; Bilici, Ahmet; Sakız, Damlanur; Özdoğan, Osman; Borlu, Fatih
Abstract : Signet cell carcinoma, which is a subtype of adenocarcinoma, usually originates from the stomach. However, it can also originate from the colon, rectum, gallbladder, pancreas, urinary bladder, and breast. We represent a 19-year-old boy diagnosed with signet cell tumour while he was being evaluated for an initial diagnosis of inflammatory bowel disease.